Corrosion Mitigation and Cathodic Protection Design for Wet Oil Processing at Qubbat Baba: A Modeling and Simulation Approach using MATLAB Simulink - Ammouri, Qays M.; Majeed, Hayder M.; Abdulkareem, Mays M.; Abdulaaima, Dhuha A.; Ibraheem, Buthaina K.; Jabur, Huda Q. (Journal of Petroleum Research and Studies, 2024)
Oil produced from Qubbat Baba in the Kirkuk oil field -North Oil Company (NOC) requires pre-treatment at the refinery due to water, mineral salts, and sediments. The water contains soluble mineral salts like sodium, calcium, and magnesium chlorides. Failure to treat the crude oil can result in operational problems, such as equipment scaling, corrosion, fouling, and catalyst poisoning in the hydrotreating unit. The study focuses on corrosion in wet oil treatment equipment especially crude oil horizontal separators (process vessels). Corrosion in the internal chamber resulted from two factors: firstly, scale deposition occurred on the surface of Galvalume (GAIII) anodes (passivation phenomenon) during oil-water separation at elevated temperatures (60°C). Secondly, the existing cathodic protection system was inadequate for the crude oil's specifications and the current field's operating conditions for separators. The XRD and XRF chemical analysis revealed that a significant portion of these deposits consisted of Al2O3 and ZnO. Based on the provided reasons, the researchers suggested a new design for the Sacrificial Anode Cathodic Protection system (SACP) using MATLAB Simulink software.